A novel add‐on collimator for preclinical radiotherapy applications using a standard cell irradiator: design, construction, and validation. Issue 6 (28th March 2020) - Fontanarosa, Davide; Benitez, Jessica; Talkhani, Sana; Fielding, Andrew; Entezam, Amir; Trapp, Jamie; Moi, Davide; Biasi, Giordano; Petasecca, Marco; Mazzieri, Roberta
Abstract : Purpose: Preclinical radiotherapy applications require dedicated irradiation systems which are expensive and not widely available. In this work, a clinical dual source 137 Cs cell irradiator was adapted to deliver 1‐cm diameter preclinical treatment beams using a lead and stainless steel custom‐made collimator to treat one or two mice at a time. Methods: The dosimetric characteristics of all the different components of the system (including collimator, phantoms, and radiation sources) have been simulated with EGSnrc Monte Carlo methods. The collimator was constructed based on these simulations and the calculated results were verified against dosimetric measurements with MO SKin detectors, GAFchromic films, and dosimetric gels. Results: The comparisons showed an agreement, in terms of full width half maximum values, between the simulated and the measured dose cross profiles at the midline within 4% for both gel dosimetry and GAFchromic films. Out of beam dose, measured in air at the collimator midplane with MOSFET detectors was between 6% and 10% of the beam axis dose. The dimensions of the beam are constant along the vertical axis of the collimator and also the simulated and measured Percentage Depth Dose (PDD) curves show an agreement within 1%. Conclusions: The collimator design developed in this work allows the creation of a beam with the necessary characteristics for ablative radiotherapy treatments on small animals using a standard clinical cell irradiator. This collimator design will make advanced preclinical studies with ablative beams possible for all those institutions which do not have collimated preclinical irradiators available.